2011
DOI: 10.4103/0019-5545.86819
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity in prisoners

Abstract: Context:The prevalence of psychiatric illness in correctional settings is significantly elevated, with higher than community rates reported for most mental disorders.Aims:(1) To examine the socio-demographic profile of convicted prisoners. (2) To evaluate the prevalence of psychiatric disorders in convicted prisoners.Materials and Methods:500 convicts were assessed for psychiatric morbidity with the help of (a) Socio-demographic proforma, (b) Pareek Udai and Trivedi G's socio-economic status scale (rural) (hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 8 publications
5
47
2
Order By: Relevance
“…Psychosis and depression were infrequent diagnosis in the present study. This was in keeping with other Indian [17] and Western studies [10,18] . Regarding Co-occurring psychiatric disorders our study sample (46%) was seen to have more than one psychiatric diagnosis at the time of assessment.…”
Section: Discussionsupporting
confidence: 91%
“…Psychosis and depression were infrequent diagnosis in the present study. This was in keeping with other Indian [17] and Western studies [10,18] . Regarding Co-occurring psychiatric disorders our study sample (46%) was seen to have more than one psychiatric diagnosis at the time of assessment.…”
Section: Discussionsupporting
confidence: 91%
“…Participants in a prison study in Iran were aged 17-76 years, with a mean age of 32.7 years [25]. The age range of the sample was 16-80 with a mean of 33.5 years in another study [26][27][28][29]. However the mean age of 36.38 in the Indian study differs but is comparable to the mean age in this study which was 33.8.…”
Section: Socio-demographic Factorsmentioning
confidence: 42%
“…Lifetime prevalence rates are 32.1% for women, 20.6% for remand and 22.6% of sentenced men. Prevalence rate was 16% in another study [27,28]. Aghaghowe, found a prevalence of 23% in a study in Benin Nigeria [24,25].…”
Section: Prevalence Of Depression Among the Prison Inmates And The Comentioning
confidence: 99%
“…A study carried out in Australia and involving 916 prisoners admitted in 2001 found that the 12-month prevalence of any psychiatric disorder in the last year was 80% in prisoners, a higher rate than the 31% was found in the community during the 1997 Australian National Survey of Mental Health and Wellbeing (n¼8168) (Butler et al, 2006). Conversely, cross-sectional studies from Brazil and India found higher rates of substance use disorders and lower rates of psychoses or mood disorders than similar studies carried out in Western countries (Pondé et al, 2011;Goyal et al, 2011). In all countries, prisoners had a higher prevalence of psychiatric disorders than the expected prevalence in the general population.…”
Section: Comparison With Past Studiesmentioning
confidence: 98%